Determination of Critical Limit of Boron for Rice, Groundnut and Potato Crops in Red and Laterite Soils of Odisha - Sarangi, Dillip Ranjan; Jena, Dinabandhu; Chatterjee, Assish Kumar (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted to assess the critical limit of boron (B) for groundnut, rice and potato in red and laterite soil (n=10) of Mayurbhanj district of Odisha. The availability of B content in the experimental soil ranged from 0.34 to 0.85 with mean value of 0.59 mg kg-1. The pH, texture, organic carbon, CEC and boron content of soil along with boron level in the third leaf and biomass yield of crops were determined after applying the recommended dose of NPK. The ten different red and laterite soils used were found to be acidic in reaction (pH 4.72−5.84), loamy sand to silt loamy texture and low to medium organic carbon content. About 30% boron deficiency was there in the examined soil samples. The critical level of B in red and laterite soils was 0.56, 0.52 and 0.56 mg kg-1 in soils for rice, groundnut and potato crop whereas for the corresponding leaves it was 23, 19 and 26 mg kg-1, respectively. The Bray’s percent dry matter yield of rice, groundnut and potato in B treated soils were varied from 52.3−118, 40.5−99 and 62−92, respectively. The maximum biomass yield was recorded in rice and groundnut at 1.5 kg B ha-1 and potato at 2.0 kg B ha-1 level indicating knowledge of critical concentration will help in maximizing the yield and performance of crop.